Susceptibility to Vibrio cholerae Infection in a Cohort of Household Contacts of Patients with Cholera in Bangladesh - Harris, Jason B.; LaRocque, Regina C.; Chowdhury, Fahima; Khan, Ashraful I.; Logvinenko, Tanya; Faruque, Abu S. G.; Ryan, Edward T.; Qadri, Firdausi; Calderwood, Stephen B. (PLOS Neglected Tropical Diseases, 2008)
BackgroundDespite recent progress in understanding the molecular basis of Vibrio cholerae pathogenesis, there is relatively little knowledge of the factors that determine the variability in human susceptibility to V. cholerae infection.Methods and FindingsWe performed an observational study of a cohort of household contacts of cholera patients in Bangladesh, and compared the baseline characteristics of household members who went on to develop culture-positive V. cholerae infection with individuals who did not develop infection. Although the vibriocidal antibody is the only previously described immunologic marker associated with protection from V. cholerae infection, we found that levels of serum IgA specific to three V. cholerae antigens—the B subunit of cholera toxin, lipopolysaccharide, and TcpA, the major component of the toxin–co-regulated pilus—also predicted protection in household contacts of patients infected with V. cholerae O1, the current predominant cause of cholera. Circulating IgA antibodies to TcpA were also associated with protection from V. cholerae O139 infection. In contrast, there was no association between serum IgG antibodies specific to these three antigens and protection from infection with either serogroup. We also found evidence that host genetic characteristics and serum retinol levels modify susceptibility to V. cholerae infection.ConclusionsOur observation that levels of serum IgA (but not serum IgG) directed at certain V. cholerae antigens are associated with protection from infection underscores the need to better understand anti–V. cholerae immunity at the mucosal surface. Furthermore, our data suggest that susceptibility to V. cholerae infection is determined by a combination of immunologic, nutritional, and genetic characteristics; additional factors that influence susceptibility to cholera remain unidentified.